Catatonia and ECT across the lifespan - Karl, Sebastian; Sartorius, Alexander; Aksay, Suna Su (Schizophrenia research, 2024)
Electroconvulsive therapy (ECT) is a safe and effective treatment for catatonia with high response rates. Although empirical data suggest that tolerability and efficacy are at least as good as in adults, ECT treatment of children, adolescents, and geriatric patients seems to pose a specific challenge for many practitioners. This article intends to explore and discuss reasons hindering the use of ECT in these patient groups, give an overview on the use of ECT to treat catatonia and provide practical advice on ECT in children, adolescents, and geriatric patients for the treatment of catatonia. Classification of catatonia as a subform of schizophrenia and a diagnostic overlap with other common conditions in children, adolescents, and geriatric patients might lead to underdiagnosis of catatonia. Concerns about the mechanism of action and about a lack of controlled studies as well as general concerns about the use of ECT in children and adolescents might lead to underutilization of ECT. However, studies of ECT to treat catatonia in children, adolescents, and geriatric patients consistently show its safety and effectiveness. Administration of ECT needs to consider some specific characteristics of children, adolescents, and geriatric patients. In conclusion, ECT is a safe and highly effective treatment for catatonia across the lifespan. Existing evidence does not warrant restrictions of its use in certain age groups.